2014
DOI: 10.3109/15419061.2014.970270
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of retrotransposon L1 in stemness and cellular plasticity

Abstract: Epithelial-to-mesenchymal transition (EMT) as well as the reverse process, mesenchymal-to-epithelial transition (MET) is important during embryogenesis. EMT is also involved in cancer invasion and metastasis, and can generate cells with properties similar to those of stem cells. Retrotransposons can rearrange the genome by inserting DNA in new loci, thus inducing mutations. This study examines the gene expression of transcription factors involved in EMT and MET. In the second experimental panel, the gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…It is not unreasonable to think that disruption of these regulatory elements following LINE-1 insertion may induce a transcriptional reprograming involving a variety of genes directly or indirectly controlling cell growth. Consistent with this view is the fact that ORF2p could modulate the expression of genes regulating epithelial to mesenchymal transition or stemness in colon cancer cells (62) and that LINE-1 inhibition induced the expression of endogenous miRNAs targeting tumor-suppressor genes in breast cancer cells (107).…”
Section: Role Of Line-1 In Tumorigenesismentioning
confidence: 91%
See 1 more Smart Citation
“…It is not unreasonable to think that disruption of these regulatory elements following LINE-1 insertion may induce a transcriptional reprograming involving a variety of genes directly or indirectly controlling cell growth. Consistent with this view is the fact that ORF2p could modulate the expression of genes regulating epithelial to mesenchymal transition or stemness in colon cancer cells (62) and that LINE-1 inhibition induced the expression of endogenous miRNAs targeting tumor-suppressor genes in breast cancer cells (107).…”
Section: Role Of Line-1 In Tumorigenesismentioning
confidence: 91%
“…The mobile nature of retrotransposons and the relatively high degree of evolutionary conservation of these sequences are certainly contributing to genome evolution (61). However, numerous studies have reported experimental evidences showing that these elements can also play a functional role in the regulation of key biological processes at the genetic or epigenetic level including tumorigenesis, though the precise mechanism by which this is occurring is not fully understood yet (55,(62)(63)(64)(65)(66). In normal differentiated tissues, LINE-1 is either not detected or is expressed at very low levels as it is maintained repressed by methylation of its promoter (67)(68)(69).…”
Section: Role Of Line-1 In Tumorigenesismentioning
confidence: 99%
“…In melanoma, expression of HERV‐K retrotransposons induces a stem cell‐like change that is characterized by higher levels of cell migration and invasion . This retrotransposon‐induced phenotype change has also been documented in the epithelial to mesenchymal transition process, which is deleterious in cancer cells as it can promote cell invasion and metastasis …”
Section: Rdgs May Regulate the Shared Features Of Placental And Camentioning
confidence: 96%
“…The most abundant RNA transposons in the human genome are LINEs (Long INterspersed Elements; about 20%) and SINEs (Short INterspersed Elements; about 13%) (Ayarpadikannan and Kim, 2014). LINE-1, which only has 100 active copies per human genome (Xiao-Jie et al, 2016), can serve as a prognostic factor of cancer progress, and even as a therapeutic target (Apostolou et al, 2015). In contrast, SINEs are non-autonomous since they do not encode proteins and require LINE-coded proteins for their propagation.…”
Section: Introductionmentioning
confidence: 99%